Principal Leadership Behavior in Improving Teacher Performance at Raudhatul Athfal (RA) Al-Barokah - Hilmi Luthfiyah; Hasyim Asy’ari (al-Afkar, Journal For Islamic Studies, 2026)
Education plays an important role in creating the progress of a nation, including in developing the character and skills of children from an early age. At the early childhood education level, the role of the principal is very crucial in improving the quality of education through the management and development of the competence of education personnel, especially teachers. This study aims to analyze the leadership behavior of the principal in improving teacher performance at Raudhatul Athfal (RA) Al-Barokah. This study uses a qualitative approach with a descriptive method, involving interviews, observations, and documentation to collect data. The results of the study indicate that the principal at RA Al-Barokah applies various leadership strategies including effective communication, coaching and motivation, creating a conducive environment, and providing adequate facilities. In addition, the principal also develops programs such as independent curriculum training, self-development workshops, teacher performance supervision, and awarding awards to encourage improvements in the quality of learning. The principal at RA Al-Barokah also emphasized the importance of performance evaluation that focuses not only on results, but also on the learning process and teacher self-development. By implementing participatory and collaborative leadership strategies, principals can create an educational environment that supports the improvement of teacher performance, which ultimately has a positive impact on the quality of learning for children. This study is expected to contribute to the development of educational leadership theory and provide practical recommendations for principals in improving the effectiveness of teacher performance at the early childhood education level.